1991
DOI: 10.1099/00221287-137-6-1431
|View full text |Cite
|
Sign up to set email alerts
|

A study of the candidate virulence factors of Bacteroides fragilis

Abstract: Bactevuides fragifis strains were classified as virulent or avirulent on the basis of their clearance from the subcutaneous tissues of mice. To determine the factors which may contribute to the virulence of B.fragifis strains, we studied encapsulation, hydrophobicity, growth rate, serum sensitivity, agglutination with erythrocytes of different origin, and neuraminidase production. The strains of the virulent group displayed a higher growth rate in broth and a lower sensitivity to the bactericidal activity of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…The capsular polysaccharide B. fragilis acts as a protector against neutrophil phagocytes and the complement bactericidal activity; it can produce abscesses in animals (Lindberg & Weintraub 1985). Moreover, all the tested strains showed characteristics such as β-hemolytic, hydrophilic, and human or horse serum resistant, in accordance with Rotimi and Eke (1984), Oyston and Handley (1990), and Namavar et al (1991).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…The capsular polysaccharide B. fragilis acts as a protector against neutrophil phagocytes and the complement bactericidal activity; it can produce abscesses in animals (Lindberg & Weintraub 1985). Moreover, all the tested strains showed characteristics such as β-hemolytic, hydrophilic, and human or horse serum resistant, in accordance with Rotimi and Eke (1984), Oyston and Handley (1990), and Namavar et al (1991).…”
Section: Discussionmentioning
confidence: 64%
“…Thus, the resistance of the B. fragilis strain against human or horse sera may explain its pathogenic potential in severe clinical infections (Rotimi & Eke 1984). Namavar et al (1991) showed that avirulent B. fagilis strains were more sensitive to serum than the virulent ones, indicating that the complement is crucial for killing of avirulent strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacteroides fragilis possui também um elevado potencial invasivo, processo que é favorecido pela produção de proteinases, neuraminidase, hialuronidases, fosfatases e DNAses (JOTWANI et al, 1991;NAKANO et al, 2007;NAMAVAR et al, 1991). …”
Section: Introductionunclassified